A DESCRIPTIVE STUDY OF USING ENGLISH SONGS IN TEACHING LISTENING TO DEVELOP STUDENTS’ VOCABULARY MASTERY AT THE TENTH GRADE STUDENTS OF IPA 1 OF MAN SRONO BANYUWANGI - Wulan Wangi; Pratiwi i Widyaning Premest; Atik Nurul Khotimah; Rohim Pradana (SOSIOEDUKASI, 2017)
This research was aimed at investigating the use of English songs in improving students’ vocabulary mastery and students’ response toward learning vocabulary through song. A descriptive qualitative research design was employed in a class consisting of 30 students at Tenth Grade of IPA 1 of MAN Srono Banyuwangi. Songs in learning activities positively promote memorizing and gaining new vocabulary easier, developing listening skill, understanding the lesson more, and expanding knowledge. The teachers can take its advantages in classroom activities to promote an effective and interesting learning atmosphere.The objective of this study is directed to improve the vocabulary mastery of the tenth grade (10) of IPA I students of MAN Srono Banyuwangi, Academic Year 2014-2015.This study applied English songs to improve the students’ vocabulary.The design of this research is Classroom Action Research (CAR) to check the students’ vocabulary improvement as well as their rate in vocabulary. This study was conducted on one cycle. It was conducted onin four meetings; three meetings were for giving treatment and implementing English songs and the other one was used for asking students’ response. The writer determined that the criteria of success the students would be successful if generally the 70% of the students’ average score were up to 61 or B. The data in this research are classified into qualitative and quantitative data. The qualitative data are taken from observation sheet, field note and students’ response sheet. Meanwhile, the quantitative data are taken from the result of listening test.